Analisis Pengaruh Beban Pajak Kini, Beban Pajak Tangguhan, dan Aset Pajak Tangguhan Terhadap Manajemen Laba - Wibowo, Dhimas Arya Pandu; Nurhayati, Nurhayati (Journal of Citizen Research and Development, 2024)
This study aims to empirically determine the effect of current tax burden, deferred tax burden, and deferred tax assets on earnings management in automotive companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The research method used is a quantitative research method. The data used are secondary data, namely financial statements registered on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample was selected using purposive sampling. Based on the determined criteria, a total of 6 automotive companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 were obtained. The analysis techniques used in this study are panel data regression analysis, panel data regression model testing, classical assumption testing, and the coefficient of determination test. The results of this study indicate that the current tax burden affects earnings management, while the deferred tax burden and deferred tax assets do not affect earnings management. Furthermore, the study found that simultaneously, the current tax burden, deferred tax burden, and deferred tax assets affect earnings management.